Morbidity and Risk Factors of Laparoscopic-Assisted Ileostomies in Children With Ulcerative Colitis. Issue 6 (June 2016) - Prato, Alessio Pini; Pio, Luca; Leonelli, Lorenzo; Pistorio, Angela; Crocco, Marco; Arrigo, Serena; Gandullia, Paolo; Mazzola, Cinzia; Sanfilippo, Fabio; Barabino, Arrigo; Mattioli, Girolamo
ABSTRACT: Introduction: Laparoscopic-assisted ileostomy (LAI) represents a cornerstone for the staged approach to ulcerative colitis (UC). The aim is to determine stoma morbidity in a series of pediatric patients and possibly identify specific risk factors. Methods: All of the patients who underwent LAI for UC between January 2008 and December 2014 were included. The following data were collected: patient demographics, preoperative medical treatment, body mass index (BMI) at surgery, Pediatric UC Index (PUCAI), and stoma-related complications. In this series of patients, a staged approach has been adopted (subtotal colectomy + ileostomy; restorative proctocolectomy with J-pouch ileo-rectal anastomosis + ileostomy; ileostomy closure). Results: Seventy-two LAIs were fashioned in 37 pediatric patients with UC. Median age at surgery was 12 years (range 5–14.8 years). Boy to girl ratio was 0.85:1. Mortality was zero. Complications occurred after 8 procedures after a median of 31 days postoperatively (range 8–60 days). Those were significantly more frequent in the case of BMI- z score >−0.51 (deleted in revised manuscript, ie, relatively overweight patients) and in the case of preoperative azathioprine administration. Pediatric UC Index score, sex, number of preoperative medications, and other preoperative parameters did not correlate with the incidence of complications. Conclusions: Our study suggests to keep a prudent behavior in the case of patients with a BMI- z score >−0.51 and received preoperative azathioprine administration. Parents should be adequately acknowledged on this regard.